Analysis of Biochemical, Hormonal and Radiological Morphological Measurement Values in Patients with Empty Sella: A Clinical Study - Alemiddin Ozdemir; Ahmet Melih Erdogan; Ozge Sevimoglu; Efe Barıs Durgun; Suha Alp Ermis; Rumeysa Yalcin; Yusuf Emin Karaca; Sevval Sila Temel; Sila Gedik; Ahmet Metehan Albayrak; Eda Istahlı; Bulent Bakar (Brazilian Neurosurgery)
Objective This study investigated the relationship between radiological morphological findings and hormone levels in patients with empty sella.